Peace Building in Communities: Experiences of a Muslim Female Social Worker in Cultivating Inter-Faith Awareness in Australia - Rashid, Amnah Khalid; Hossain, Ishtiaq (IIUM Press, 2019)
Abstract: In 2007, the United Nations (UN), following a lengthy debate, expanded the definition of peace-building, to one that was not only comprehensive, but more crucially described it as a long term process involving different actors, and institutions. The UN also encouraged the acceptance of many of the indigenous approaches and strategies in managing different types of conflicts. In that definition women were recognized as a key factor in peacebuilding. Their participation was encouraged by adopting UN Resolution 1325, which was to be implemented through National Action Plan by signatories. This paper focuses on community level peacebuilding mechanism in multicultural societies to build social cohesion through inter-faith dialogue, awareness and education in Australia. Using interview method to relate a Muslim woman’s experience of building peace at community level, the paper describes the works of Dr. Nora Amath and her organization Australian Muslim Advocates for the Rights of All Humanity (AMARAH). The paper analyses the approaches and strategies used by AMRAH to build trust between Muslims and non- Muslims in inter-faith dialogue towards building peace and tolerance among the communities in Brisbane. The remarkable success of community leaders like her in maintaining openness to communication, respect and tolerance won her the Australian 2015 Peace Woman of the Year Award. Keywords: Peacebuilding, women, Dr. Nora Amath, AMARAH, Australi